Optimalisasi Bekerjanya Pengungkapan Dana Kampanye sebagai Strategi Pencegahan Politik Uang - Prasetyo, Wegik (Komisi Pemberantasan Korupsi, 2019)
Campaign finance disclosure in Indonesia has received attention from the post-Soeharto elections with the issuance of various regulations related to revenue, expenditure, reporting of campaign funds by the General Election Commission. However, the application of campaign finance disclosures has never been optimized. This article contributes to overcoming two problems at once. First, conceptually, the study of disclosure of campaign funds was dominated by disclosure of campaign funds at the level of political parties and legislative elections. This article focuses on knowing how the application of campaign finance disclosure at the level of regional head elections, using the case of the 2018 regional election. Second, in practice, there are problems in regulation, implementation and understanding of the practice of campaign finance disclosure in Indonesia. This article explains why campaign finance disclosure has never been optimized and always has a strong correlation with the failure to prevent money politics. The author argues that prevention of money politics can be done by optimizing the operation of disclosure of campaign funds. As long as the disclosure of campaign funds is not optimal, so far the prevention of money politics will not be effective. Keywords: Money Politics, Campaign Finance Disclosure, Veiled Political Spending, Dark Money